Mind my language - Abdul Ghani, Che An (Universiti Putra Malaysia Press, 2016)
Language and brain are two entities that are intricately dependent on one another. Language is a tool for expressing thoughts, emotions, interactions, and a host of other human activities. Without a good functioning brain, human cannot operate the above activities. Scientists have conducted many experiments on brain and language development in children, adults and chimpanzees. This branch of science that studies brain and language is known as neurolinguistics.